Comparing Holland and Self-Determination Theory Measures of Career Preference as Predictors of Career Choice. (February 2020) - Sheldon, Kennon M.; Holliday, Greyson; Titova, Liudmila; Benson, Craig
John Holland's theory of career orientations advises people to select careers that are congruent with their personalities. Similarly, self-concordance theory, based in self-determination theory, advises people to select personal goals that match their autonomous interests and identifications. We compared the predictive efficacy of the two theories in two studies of undergraduates, using the six career areas of Holland theory (RIASEC: realistic, investigative, artistic, social, enterprising, and conventional) as a common base. Multilevel logit modeling in Study 1 showed that both the Holland score and an aggregate self-concordance score predicted independent variance in the outcome variable, current career choices. These effects were replicated in Study 2. Supplementary analyses showed that the identified motivation subscale was the primary source of these effects. Thus, career counselors may want to consider assessing students' self-concordance for the six RIASEC domains, in particular their levels of identified motivation for those domains, in addition to assessing their Holland codes.